Virtual colonoscopy and abdominal imaging computational challenges and clinical opportunities : second international workshop held in conjunction with MICCAI 2010, Beijing, China, September 20, 2010, revised selected papers - International Workshop on Computational Challenges and Clinical Opportunities in Virtual Colonoscopy and Abdominal Imaging Beijing, China) 2010; Yoshida, Hiroyuki 1961-.; Cai, Wenli; SpringerLink (Online service).; International Conference on Medical Image Computing and Computer-Assisted Intervention Beijing, China) 2010 (Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the International Workshop on Computational Challenges and Clinical Opportunities in Virtual Colonoscopy and Abdominal Imaging, held in conjunction with MICCAI 2010, in Beijing, China, on September 20, 2010. The 19 revised full papers presented were carefully reviewed and selected from 26 submissions. The papers are organized in topical sections on CT colonography CAD, abdominal imaging, and virtual colonoscopy.
Electronic reproduction.
Keywords: Colon (Anatomy) -- Tomography